Transcription of Former Architecture - Zinoski, M., Dimitrievski, T. (University of Pécs Faculty of Engineering and Information Technology, 2019)
Nowadays architectural practice deals with compromising the creation of new forms striving for self-sustainability, energy efficiency etc. and respecting the existing historical monuments that carry on the spirit that users identify with. The case study of this paper is a direct consequence of the physical appearance, through the objective reality that is being stimulated by the contemporary needs, articulating the demands of the new users. Those necessities transform the original architectural concept beyond recognition. This problem of sustainable preservation emphasizes the significance of architectural identity and develops new spatial needs of the actual users. The modernistic ideology lead by its strict apriority has no impact over forming social cohesion. Considering architecture is a communication medium, the method of transcription tends to strengthen the connection between the newly ingrained program and the community's requirements on a local scale. Generating architectural methods that complete the task of both constant sustainability and social cohesion sets the fundamentals for creating synergies as a collective awareness in a world of constant changes.
Keywords: Concept, Transcription, Cohesion, Typology, Identity